PENGEMBANGAN MEDIA BERBASIS FLASH CARD AUGMENTED REALITY PADA MATERI KEBERAGAMAN BUDAYA INDONESIA UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS V SD NEGERI BHAYANGKARA - Ridha Artsani Ksvara; Rian Nurizka (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop Augmented Reality-based Flashcard media on Indonesian Cultural Diversity material and to examine its feasibility, practicality, and effectiveness in enhancing the learning interest of fifth-grade students. The research employed a Research and Development (R&D) method using the ADDIE model. The subjects consisted of 26 students in the control class and 27 students in the experimental class at SD Negeri Bhayangkara. Data were collected through expert validation questionnaires, teacher and student response questionnaires, learning interest questionnaires, and pretest-posttest, then analyzed using validity, reliability, normality, homogeneity tests, Independent Samples t-test, and N-Gain. Validation results indicated that the media was highly feasible (material expert 4.27; media expert 4.84). The media was also found to be highly practical based on teacher responses (4.333) and student responses (4.41). The effectiveness test showed a significant difference in learning interest (Sig. 0.000 < 0.05), with an N-Gain of 71.08 (high) in the experimental class and 28.10 (low) in the control class. Therefore, the Augmented Reality-based Flashcard media is declared highly feasible, highly practical, and effective in enhancing students’ learning interest.